Mawaqif al- Mu’minina fi Ghozwati Tabuuk Min Khilaali Surah At-Taubah - Mubarok Ibrahim At-Tijani (ADP Publisher, 2024)
Jihad in the name of Allah with one's soul and wealth has various forms and rulings that are mentioned in many verses of the Holy Quran. The Prophet Muhammad (peace be upon him) and his. One of the battles mentioned in the Holy Quran in Surah At Tawbah is the Battle of Tabuk and the events that took place there, as well as the lessons learned from it. The aim of this research is to review this battle and extract some of its lessons and conclusions using the analytical and descriptive approach. One of the most important results that the researcher reached is that this battle took place outside the Hijaz region, which required travel and effort, thus testing the determination of the believers. One of the greatest lessons learned is that the Prophet Muhammad (peace be upon him) used to live with the soldiers through all the hardships. The Companions (may Allah be pleased with them) presented the best models in their quick response to Allah and His Messenger, even though some delayed their departure for various excuses.